Cycle of life and Virus19 Effect for Worthy of Human - Nam Prasert, Phra Khru Si Thammawaraporn Thamapasattho (Wishing Journal Review, 2023)
What is theVirus19 given reason for human remind? We all know well for this case as the same of antiacne disease up to now. But nowadays it rather awful more than before. Example for corona-19 come from biological weapon. So that disease from nowadays has been more before such as 2nd world war was attracted human by bad weapon (Nuclear). Therefore, corona-19 must be awful and ugly more than before. Event everyday life for close people cannot be meet and communicate on face then died because of this disease the cremate them. In the ancient time at Visary city had been got crisis like this too. From their bodies as concern with corona-19 had been “In Humans” or date of spirit as all cover places.